1991
DOI: 10.1002/tera.1420430309
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lysosomal proteinase inhibition on the development of the rat embryo in vitro

Abstract: Altered lysosomal function in the visceral yolk sac can result in abnormal development. As proteolysis is an important function of the rodent visceral yolk sac during early and mid-gestation, we characterized the lysosomal proteolytic enzyme activity of this extraembryonic membrane and determined the effects of inhibitors of protein degradation on embryonic development. Constituent activities of cysteine and aspartic acid proteinases were measured in rat visceral yolk sac on gestation day 12, and the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…D, the protein is also localized on the surface (arrowheads) of the late-stage embryos (emb) (bar, 500 nm). inhibitors E-64 or leupeptin, resulted in decreased protein processing and embryo growth retardation in rat (37), confirming the postulated role of cathepsin L for normal breakdown of proteins during embryogenesis in this system (38). In C. elegans this potential function is supported by preliminary studies that have shown defects in yolk processing in Ce-cpl-1 RNAi mutant embryos.…”
Section: Figsupporting
confidence: 55%
“…D, the protein is also localized on the surface (arrowheads) of the late-stage embryos (emb) (bar, 500 nm). inhibitors E-64 or leupeptin, resulted in decreased protein processing and embryo growth retardation in rat (37), confirming the postulated role of cathepsin L for normal breakdown of proteins during embryogenesis in this system (38). In C. elegans this potential function is supported by preliminary studies that have shown defects in yolk processing in Ce-cpl-1 RNAi mutant embryos.…”
Section: Figsupporting
confidence: 55%
“…In regard to lysosomal degradation of yolk precursors, the activities of lysosomal proteases cathepsin B and D have been shown to be high in the endodermal cells of the quail yolk sac (45). Furthermore, inhibition of the rat visceral YS lysosomal proteinases cathepsin B and L result in a decrease in embryonic growth and an increase in fetal abnormalities, including neural tube defects (46).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, various proteolytically processed hormones and growth factors are involved in growth and differentiation. It has been shown consistently that inhibition of cysteine proteases produces a concentrationdependent decrease in embryonic growth and an increase in abnormalities (Daston et al, 1991).…”
Section: Introductionmentioning
confidence: 99%